Endovascular stenting of the obstructed vertical vein in a neonate with supracardiac total anomalous pulmonary venous return - Nageswara R Koneti; Hemasree Kandraju; Vasudevan Kanchi; Sreenivas Kumar Arramraju (Annals of Pediatric Cardiology, 2012)
A newborn baby presented with respiratory distress, cyanosis and shock within 2 hours of birth. The cardiac evaluation showed supracardiac total anomalous pulmonary venous return with critically obstructed vertical vein. The baby underwent successful stenting of the vertical vein at 12 hours of life.